2017
DOI: 10.22159/ijpps.2017v9i12.21835
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial Activity of Selected Underutilized Plants and Cytotoxic Property of Terminalia Catappa

Abstract: Objective: This study aimed at determining the antibacterial activity of the underutilized plants of Sri Lanka, “Kottamba” (Terminalia catappa), “Purpurata” (Alpinia purpurata) and “Harankaha” (Curcuma zedoaria), against food-borne pathogens. Chemical composition and in vitro cytotxicity of the most active antibacterial plant extract(s) were examined.Methods: Crude rhizome extracts were obtained for all plants whereas in respect of T. catappa, the red pericarp of the fruit was used. The antibacterial activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Our study reports the significant inhibition of the test pathogens at a very less concentration in particular reference to MRSA and S. aureus (clinical isolate). Other research suggested that the polar extracts such as methanol and ethanol have great inhibitory activity against Gram-positive organisms [71,72], which can be correlated with the present study reporting on the acetone extract, a polar component, exhibiting significant inhibitory activities. The activity of the polar extracts was reported due to the presence of a high level of water-soluble tannins in T. catappa which generally exhibit antibacterial activity [73].…”
Section: Discussionsupporting
confidence: 91%
“…Our study reports the significant inhibition of the test pathogens at a very less concentration in particular reference to MRSA and S. aureus (clinical isolate). Other research suggested that the polar extracts such as methanol and ethanol have great inhibitory activity against Gram-positive organisms [71,72], which can be correlated with the present study reporting on the acetone extract, a polar component, exhibiting significant inhibitory activities. The activity of the polar extracts was reported due to the presence of a high level of water-soluble tannins in T. catappa which generally exhibit antibacterial activity [73].…”
Section: Discussionsupporting
confidence: 91%